Dipeptidyl peptidase-4 inhibitor anagliptin reduces fasting apolipoprotein B-48 levels in patients with type 2 diabetes: A randomized controlled trial - Onoue, Takeshi (PLoS One, 2020)
Type 2 diabetes and dyslipidemia are diseases that collectively increase the risk of patients developing cardiovascular complications. Several incretin-based drugs are reported to improve lipid metabolism, and one of these medications, anagliptin, is a dipeptidyl peptidase-4 (DPP-4) inhibitor that has been shown to decrease serum triglyceride and low-density lipoproteins cholesterol. This study aimed to conduct an investigation into the effects of anagliptin on serum lipid profiles. This multicenter, open-label, randomized (1:1), parallel group study was designed to evaluate the effects of anagliptin on serum lipid profiles (triglycerides, lipoproteins, apolipoproteins, and cholesterol fractions). The study involved 24 patients with type 2 diabetes at two participating hospitals for a period of 24 weeks. Patients were randomly assigned to the anagliptin (n = 12) or control (n = 12) groups. Patients in the anagliptin group were treated with 200 mg of the drug twice daily. Patients in the control group did not receive anagliptin, but continued with their previous treatment schedules. Lipid metabolism was examined under fasting conditions at baseline and 24 weeks. Patients treated with anagliptin for 24 weeks exhibited significantly reduced levels of serum apolipoprotein B-48, a marker for lipid transport from the intestine, compared with the control group patients (P < 0.05). After 24 weeks of treatment, serum adiponectin levels were significantly raised, whereas glycated hemoglobin (HbA1c) levels were significantly lower compared with the baseline in the anagliptin group (P < 0.05), but not in the control group. This study showed that the DPP-4 inhibitor anagliptin reduces fasting apolipoprotein B-48 levels, suggesting that this drug may have beneficial effects on lipid metabolism possibly mediated by the inhibition of intestinal lipid transport.